Сontribution of Imaging Techniques for Patient's Safety in Anesthesiology Practice (Review) - Andrey Yu. Zaitsev; Kyrill V. Dubrovin; Vsevolod A. Svetlov (Общая реаниматология)
Medical imaging deals with physical examination and visual monitoring the organs and tissues. The main advantage of the imaging is capability to get quick and informative diagnostic data on the state of the main body systems in real time. In addition, imaging system using can reduce the risk of complications during manipulations. In this review, the potential of various imaging techniques, their advantages and disadvantages, and features of their application in anesthesiology are discussed.